Synchronization degree of a two-compartment neuron based on transcranial magnetic stimulation - Pu Chen; Quan Yuan (Results in Physics, 2024)
Synchronization is a very important phenomenon in the nervous system, which is closely related to the encoding, integration and transmission of information. In this paper, synchronization and transition of a two-compartment respiratory neuron model under transcranial magnetic stimulation (TMS) are studied from the perspective of synchronization degree for the first time. We are established the correlation degree with synchronization, and discussed the firing mode and transition rule of the neurons in the two-compartment compartment pre-Bötzinger complex (PBC) by means of bifurcation theory and Lyapunov index. The results show that the synchronization of neurons has a great influence under TMS, which is embodied in the fact that the somatic will experience a peak firing and a transition from bursting to resting under the magnetic stimulation,which was a phenomenon never before shown in PBC neurons. These results fully reveal the dynamic behavior of PBC nervous system under TMS, and provide theoretical value for further understanding of respiratory rhythm.